Association of Gastric Acid Suppression and Sorafenib Efficacy in Advanced Hepatocellular Carcinoma. Issue 2 (February 2021) - Razak, Razwan A.; Fletcher, Peter; Kunene, Victoria; Ma, Yuk Ting
Abstract : Background: Recent studies have revealed that coadministration of gastric acid suppressants reduces the efficacy of the tyrosine kinase inhibitors erlotinib and sunitinib in patients with non–small cell lung cancer and renal cell carcinoma, respectively. The authors have therefore assessed if the concurrent use of gastric acid suppressants and sorafenib impairs outcomes in patients with advanced hepatocellular carcinoma (HCC). Methods: A retrospective analysis was conducted on all patients treated with sorafenib for advanced HCC at a single tertiary referral unit in the United Kingdom, between January 2008 and January 2014. A multivariate Cox proportional hazard model was used to assess the effect of the concomitant use of gastric acid suppression and sorafenib on progression-free survival (PFS) and overall survival (OS). Results: Data were collected from 197 patients, of which 182 could be assessed for this study; 77 (42%) were on concurrent gastric acid suppression therapy. After adjusting for imbalances between the groups, a Cox regression analysis gave an adjusted hazard ratio for the concurrent acid suppression group compared with the no acid suppression group of 5.4 (95% confidence interval, 3.6-7.9) for PFS and 1.85 (95% confidence interval, 1.3-2.6) for OS. Conclusions: This single-center experience shows that patients with advanced HCC taking sorafenib and concomitant gastric acid suppression therapy have significantly inferior PFS and OS. This is the first time that this negative interaction has been reported and further prospective validation is warranted. Abstract : Supplemental Digital Content is available in the text.